Chinese photographers and their clientele in the Netherlands Indies, 1890-1940 - Ouwehand, Liesbeth (UI Scholars Hub, 2017)
This article examines the position of Chinese photographers in the visual colonial landscape. The Chinese toekang potret were involved in both commissioned photographs and the production of commercial images, but the latter was less widespread. Contrary to the image that Chinese photographers' clients were from the lower strata of society, this article shows that they were commissioned by the European, Chinese and Javanese elite. The image materiality of the portraits reveals the visual traces of circulation and exchange. Hence, the Chinese photographers were indirectly involved in these elite networks as well.